Design and Development of a VR Wheelchair game with Redirect Movement - Sassi, Victor; Clua, Esteban; Trevisan, Daniela; Porcino, Thiago (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2024)
In this paper, we explore the development and design of an accessible virtual reality (VR) game aimed at fostering empathy for wheelchair users, and to simulate their challenges. The game design integrates a novel redirect movement system, enabling realistic locomotion within a virtual space without extensive physical movement. This system, developed using only an all-in-one head-mounted display (HMD), adjusts the user's position seamlessly to maintain immersion and comfort within three scenarios. This work contributes to the broader field of VR accessibility and serves as a model for developing inclusive VR applications that cater to diverse user needs. Future directions include developing and evaluating additional games.